MANAGEMENT OF HPV RELATED OROPHARYNGEAL CANCER-A REVIEW ABOUT TREATMENT (Journal of Medical & Health Sciences Review, 2025)
Human papillomavirus (HPV)-associated oropharyngeal cancer (OPC) has emerged as a growing public health concern worldwide. This review focuses on the current understanding and management strategies for HPV- related OPC. The rising incidence of this malignancy highlights the need for comprehensive insight into its epidemiology, transmission, etiology, genomic organization, pathogenesis, diagnostic methods, and available treatment options. The article examines conventional and emerging therapeutic   approaches,   including   chemoradiotherapy   (CRT), Naeem, Institute of Microbiology, immunotherapy, surgical innovations, and targeted medical treatments. Government College University Faisalabad, Pakistan,Email: jazabjutt2022@gmail.comNotably, recent progress in immunotherapeutic interventions has shown encouraging potential in improving treatment outcomes. This review also addresses the effectiveness and side effects of these therapies, with particular attention to their impact on patients' quality of life and long-term survivorship. Additionally, it underscores the critical role of HPV vaccination in primary prevention and provides an overview of ongoing clinical trials. The insights presented aim to support clinicians, healthcare professionals, researchers, and policymakers in enhancing the management and prevention of HPV-related OPC.